WORD-FORMATION FEATURES OF HYBRID WORDS FORMED ON THE BASIS OF ANGLICISMS IN THE ECONOMIC VOCABULARY OF THE UZBEK LANGUAGE - Abdukakharova Gulnoza Abduvahobovna (Western European Studies, 2025)
The article examines Anglicism-based hybrid lexical units emerging in Uzbek economic vocabulary. The study aims to identify the word-formation patterns of these hybrids, describe their structural and semantic features, and clarify their functional potential in economic discourse. The analysis treats affixation and composition as the main mechanisms of hybrid formation. In particular, the productivity of affixational patterns such as X+chi, X+lik, X+lash, and X+li is discussed, along with the terminologization potential of compositional structures including N+N, Adj+N, and N+Adj. The findings show that hybrid units differ from ordinary loanwords because they generate new nominations through the derivational adaptation of a borrowed component within the Uzbek word-formation system. This tendency is associated with communicative economy in the economic domain, rapid naming needs, and the demand for unified normative spelling and usage criteria. The paper also proposes practical criteria for distinguishing hybrid units from barbarisms, calquing, and code-switching in lexicographic and terminological practice
Keywords: anglicism; hybrid unit; economic vocabulary; word formation